Optimal spirometry thresholds for the prediction of chronic airflow obstruction: a multinational longitudinal study - Abby H.S. Lam; Sheikhah A. Alhajri; James Potts; Imed Harrabi; Mahesh Padukudru Anand; Christer Janson; Rune Nielsen; Dhiraj Agarwal; Andrei Malinovschi; Sanjay Juvekar; Meriam Denguezli; Thorarinn Gislason; et al. (ERJ Open Research)
Introduction Chronic airflow obstruction is key for COPD diagnosis, but strategies for its early detection are limited. We aimed to define the optimal z-score thresholds for spirometry parameters to discriminate chronic airflow obstruction incidence. Methods The Burden of Obstructive Lung Disease study is a multinational cohort study. Information on respiratory symptoms was collected and pre- and post-bronchodilator spirometry was performed at baseline. 18 study sites were followed-up with repeat measurements after a median of 8.4 years. We converted lung function measurements into z-scores using the Third National Health and Nutrition Survey reference equations. We used the Youden index to calculate the optimal z-score thresholds for discriminating chronic airflow obstruction incidence. We further examined differences by smoking status. Results We analysed data from 3057 adults (57% female, mean age: 51 years at baseline). Spirometry parameters were good at discriminating chronic airflow obstruction incidence (area under the curve 0.80–0.84), while respiratory symptoms performed poorly. The optimal z-score threshold was identified for pre-bronchodilator forced expiratory volume in 1 s to forced vital capacity ratio (FEV1/FVC) <−1.336, equivalent to the 9th percentile (sensitivity: 78%, specificity: 72%). All z-score thresholds associated with a lower post-bronchodilator FEV1/FVC and greater odds of chronic airflow obstruction at follow-up. The risk of chronic airflow obstruction was slightly greater for current smokers and, to some extent, never-smokers with a pre-bronchodilator FEV1/FVC <9th/10th percentiles at baseline, particularly among males. Conclusions Spirometry is better than respiratory symptoms at predicting chronic airflow obstruction incidence. A pre-bronchodilator FEV1/FVC <9th/10th percentiles, particularly among current smokers, could suggest early airflow obstruction or pre-COPD.